A glycated whey protein isolate–epigallocatechin gallate nanocomplex enhances the stability of emulsion delivery of β-carotene during simulated digestion. Issue 10 (3rd October 2019) - Wang, Qi; Li, Wanrong; Liu, Pei; Hu, Zhongze; Qin, Xinguang; Liu, Gang
Abstract : A glycated whey protein isolate–epigallocatechin gallate (EGCG) nanocomplex-stabilized emulsion was used to encapsulate β-carotene. Abstract : A glycated whey protein isolate–epigallocatechin gallate (EGCG) nanocomplex-stabilized emulsion was used to encapsulate β-carotene. This study evaluated the stability of the emulsion in different environments and assessed its protective effect on β-carotene. The active compound-loaded emulsion was subjected to in vitro simulated digestion. The results show that the glycated whey protein isolate–EGCG nanocomplex-stabilized emulsion has greater storage, salt ion, and thermal stability than the whey protein isolate–EGCG nanocomplex. Moreover, the emulsion exerts a considerable inhibitory effect on the degradation of the active compounds. However, the strong hydrolysis of the protein by pancreatin prevents the emulsion from surviving in the intestinal fluid, and the speed and degree of lipolysis is faster and more intense than that of naked medium-chain triglyceride (MCT). This study provides useful information for the application of natural hydrophobic active ingredients to water-soluble edible protein emulsion systems in food and drug delivery.